O sistema educacional que provocou o movimento estudantil a reinvidicar sua reforma no início da década de 1960 - Braggio, A. K. (2020)
In this study we present the basic aspects of the Brazilian education context of the 1960s, mainly at the higher level. However, attention to the other levels, primary and secondary, is essential to understand the existing bottleneck in Brazilian education, caused by social, economic and financial order. Thus, an educational system of social privilege, highly criticized by the student movement at the time, sought to meet the needs and interests of the class and not the expansion of scientific and technological education, indispensable for social progress and economic growth. To support this contextualization, we chose to use statistical data as an interpretative resource. Based on these quantitative data, it was possible to diagnose the development of the educational system and present the situation it was in during the 1960s.